Implementing a Deep Learning Approach in Local Cultural Arts Education for Early Childhood: A Qualitative Study in Yogyakarta - Riska Avi Aryani; Joko Pamungkas (GENIUS: Indonesian Journal of Early Childhood Education, 2025)
This study examines the implementation of a deep learning approach in local cultural arts education for early childhood within a kindergarten setting in Yogyakarta. Using a qualitative descriptive design, data were collected through classroom observations, teacher interviews, and documentation. The analysis focused on key dimensions of deep learning, including meaningful learning, active exploration, collaboration, and reflective practice. The findings indicate that integrating local cultural arts through a deep learning–oriented approach supports children’s engagement, creativity, cultural awareness, and social interaction. Learning activities encouraged children to explore artistic processes, express ideas, collaborate with peers, and engage in simple reflection on their experiences. Teachers played a central role in facilitating inquiry-based and contextually relevant learning environments. However, challenges emerged related to teachers’ understanding of deep learning principles, limited instructional time, and constraints in learning resources. This study highlights the contextual potential of deep learning approaches to strengthen culturally responsive pedagogy in early childhood education and provides practical insights into the implementation of arts-based learning grounded in local culture.